Brachial artery flow mediated dilation and pulsatility index change as independent predictors for hypertensive disorders in the second trimester of pregnancy. (May 2016) - Praciano De Sousa, Paulo César; Gurgel Alves, Júlio Augusto; Bezerra Maia E Holanda Moura, Sammya; Araujo Júnior, Edward; Martins, Wellington P.; Da Silva Costa, Fabricio
Abstract: Objective: To assess brachial artery flow mediated dilatation (FMD) and pulsatility index change (PIC) as independent parameters for prediction hypertensive disorders (preeclampsia – PE and gestational hypertension – GH) in the second trimester of pregnancy. Study design: We performed a prospective cohort study with 372 singleton pregnant women who underwent routine second trimester morphology scan. FMD and PIC were measured immediately after the ultrasound scan using the following formulas: FMD (%) = [(post occlusion arterial diameter − baseline arterial diameter)/baseline arterial diameter] × 100 and PIC (%) = [(pulsatility index pre − pulsatility index post)/pulsatility index pre]. The control and hypertensive disorder groups were compared using the Kruskal–Wallis to continue variables and Chi-square and Fisher exact tests to categorical variables. We assessed the predictive accuracy of FMD and PIC by the area under the receiver operating characteristics (ROC) curve with its respective 95% confidence interval (CI). Results: We did not observe statistical difference between control and hypertensive disorder groups regarding the FMD and PIC ( p = 0.17 and p = 0.38, respectively). Areas under ROC curve for prediction of GH using FMD and PIC were 0.59 (CI95% 0.48–0.71) and 0.60 (CI95% 0.47–0.73), respectively. Areas under ROC curve for prediction of PE using FMD and PIC were 0.55 (CI95% 0.46–0.64) and 0.52 (CI95% 0.61–0.69), respectively. Conclusion: Brachial artery FMD and PIC as independent parameters did not show good prediction for hypertensive disorders in the second trimester of pregnancy.